DIDACTIC POTENTIAL OF INTERNET-TECHNOLOGY «PODCASTING» IN TEACHING FOREIGN LANGUAGE LISTENING IN UPPER SECONDARY SCHOOL - Andrey Vatunsky; Nonna Pelevina (Вестник Северо-Кавказского федерального университета)
This article describes the features of teachingforeign language listening in upper secondary school, points out the conditions of the organization of teaching listening with the help of Internet-technology «Podcasting». The article presents science-based characteristics of the podcasts technology in teaching foreign language listening, which include special exercises at all stages of learning. This technology promotes developing and improving students' auditive skills which in their turn provide a basis for further use in the professional activity.